Primary wall cellulose synthase regulates shoot apical meristem mechanics and growth - Sampathkumar, Arun; Peaucelle, Alexis; Fujita, Miki; Schuster, Christoph; Persson, Staffan; Wasteneys, Geoffrey O.; Meyerowitz, Elliot M. (Development (Cambridge), 2019)
How organisms attain their specific shapes and modify their growth patterns in response to environmental and chemical signals has been the subject of many investigations. Plant cells are at high turgor pressure, and are surrounded by a rigid yet flexible cell wall, which is the primary determinant of plant growth and morphogenesis. Cellulose microfibrils, synthesized by plasma membrane-localized cellulose synthase complexes, are major tension-bearing components of the cell wall that mediate directional growth. Despite advances in understanding genetic and biophysical regulation of morphogenesis, direct studies on cellulose biosynthesis and its impact on morphogenesis of different cell and tissue types are largely lacking. In this study, we take advantage of mutants of three primary cellulose synthase (CESA) genes that are involved in primary wall cellulose synthesis. Using field emission scanning electron microscopy, live cell imaging and biophysical measurements, we aimed to understand how the primary wall CESA complex acts during shoot apical meristem development. Our results indicate that cellulose biosynthesis impacts the mechanics and growth of the shoot apical meristem.